Changing trade patterns after conflict resolution in South Caucasus - Polyakov, Evgeny (Policy research working paper, 2001)
Peace in the South Caucasus will improve the region's economies in different ways. How much they will benefit depends on the strength of their supply response to demand in opening markets. The poor business environment and incomplete industrial restructuring act as constraints on export performance